Telecollaboration to Improve CLIL and TPACK Knowledge: Aid or Hindrance? - Mª Camino Bueno-Alastuey; Soraya García Esteban (Universidad de Navarra, 2016)
This paper reports on a pilot study on the use of telecollaboration to develop TPACK through the joint analysis of CLIL units created by groups of teacher trainees. The instruments to collect the data were a questionnaire, chat transcripts and a voice recording. Quantitative and qualitative data were analysed to explore type of TPACK episodes taking place, type of telecollaboration, changes or suggestions for improvement of CLIL units, and perceived advantages and constraints of the telecollaboration. Results suggest students' attention focused on technology while talking about the telecollaboration, but on pedagogy and content when talking about the unit.